2017
DOI: 10.1111/cen3.12405
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic system and gut microbiota affect immunopathology of neuroinflammatory diseases, including multiple sclerosis, neuromyelitis optica and Alzheimer's disease

Abstract: Microbial infections lead to neurological damages either by direct infection in the nervous tissues or by uncontrolled immune responses (immunopathology). For example, in Zika virus infection, microcephaly can be caused by the former, i.e., direct viral infection in the brain, while Guillain-Barré syndrome (GBS) seems to be antibody-mediated immunopathology. Although a variety of factors affect immunopathology, two essential systems maintaining whole-body homeostasis had long been neglected: 1) the lymphatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Experimental intracerebral infection of young adult mice causes flaccid paralysis of the hind limbs [3,7]. The course of Theiler’s murine encephalitis (TME) depends on the virus and mouse strains as well as other factors including intestinal microbiota and stress [3,14,15,16,17]. Mice develop an acute polioencephalomyelitis within two weeks following experimental intracerebral TMEV infection.…”
Section: General Aspects Of Theiler’s Murine Encephalomyelitis Virusmentioning
confidence: 99%
“…Experimental intracerebral infection of young adult mice causes flaccid paralysis of the hind limbs [3,7]. The course of Theiler’s murine encephalitis (TME) depends on the virus and mouse strains as well as other factors including intestinal microbiota and stress [3,14,15,16,17]. Mice develop an acute polioencephalomyelitis within two weeks following experimental intracerebral TMEV infection.…”
Section: General Aspects Of Theiler’s Murine Encephalomyelitis Virusmentioning
confidence: 99%
“…It was found that the ablation of intestinal lacteals disrupted blood vessel and villous architecture, which lead to increased invasion of intestinal pathogens into the circulatory system [ 80 ]. Indeed, common disease states like IBS and IBD have been shown to reduce the functionality of lymphatic vessels as well [ 81 , 82 ]. As discussed previously, this, therefore, may induce systemic inflammation and subsequent neuroinflammation.…”
Section: Gut-induced Inflammation and Altered Neuroimmunologymentioning
confidence: 99%
“…When the activation of the immune system is appropriate, this contributes to the elimination/regulation of microbes. Dysbiosis, an altered state of bacterial community, has been associated with health conditions and diseases ( 16 , 17 ). Dysbiosis could lead to excessive activation of the immune system; uncontrolled immune responses can cause immunopathology, particularly in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%